F806 Suppresses the Invasion and Metastasis of Esophageal Squamous Cell Carcinoma via Downregulating F-Actin Assembly-Related Rho Family Proteins. (19th September 2018) - Xie, Lei; Li, Li-Yan; Zheng, Duo; Xie, Yang-Min; Xu, Xiu-E; Tao, Li-Hua; Liao, Lian-Di; Xie, Ying-Hua; Cheng, Yin-Wei; Xu, Li-Yan; Li, En-Min
Abstract : Invasion and metastasis are critical pathological and mortal processes in esophageal squamous cell carcinoma (ESCC). Novel drugs, targeting the two cancer migration stages, will augment the treatment options for ESCC therapy and improve overall survival. A novel natural macrolide F806 specifically promotes apoptosis of various ESCC cells. However, whether F806 can inhibit metastasis of ESCC cells needs further evaluation. Here, our data showed that F806 inhibits dynamic F-actin assembly and then suppresses the migration of ESCC cells in vitro and their invasion and metastasis in vivo. The correlation between cancer migration and actin cytoskeleton assembly was consistent with the ability of F806 to prevent the aggregation of Paxillin, an essential protein for focal adhesion formation through binding to the ends of actin filaments. Furthermore, F806 downregulated the expression and activity of the Rho family proteins cell division cycle 42 (CDC42), RAC family small GTPase 1 (RAC1), and RAS homolog family member A (RHOA). Taken together, these results suggest that F806 can suppress cancer invasion and metastasis via interrupting the assembly of migration components involving F-actin.